Reclaiming The Human- Nature Communion: An Ecological Quest In Witi Ihimaera’s The Matriarch. - Anil kumar, Kavya (International Journal of Psychosocial Rehabilitation, 2020)
AbstractMaori literature focuses on the sacred communion of human beings and the mother-Nature. The disastrous effects caused by colonialism on the Maori community are vividly portrayed by the dominant Maori writers such as Witi Ihimaera, Alan Duff, Patricia Grace and Keri Hulme. The eternal urge to reclaim the lost identity is discussed in their works. Nature is given the supreme role in Maori literature. One of the appropriate instances is Witi Ihimaera’s The Matriarch (1986). Witi Ihimaera analyses how the ravaging effects of colonialism deformed the identity of the Maori community. This article analyses Witi Ihimaera’s The Matriarch and attempts to unveil the changes brought by colonialism on the environment and the efforts taken by the Maori people to reclaim the land as well as their true identity.